2021
DOI: 10.1038/s42003-021-01928-2
|View full text |Cite
|
Sign up to set email alerts
|

An engineered ligand trap inhibits leukemia inhibitory factor as pancreatic cancer treatment strategy

Abstract: Leukemia inhibitory factor (LIF), a cytokine secreted by stromal myofibroblasts and tumor cells, has recently been highlighted to promote tumor progression in pancreatic and other cancers through KRAS-driven cell signaling. We engineered a high affinity soluble human LIF receptor (LIFR) decoy that sequesters human LIF and inhibits its signaling as a therapeutic strategy. This engineered ‘ligand trap’, fused to an antibody Fc-domain, has ~50-fold increased affinity (~20 pM) and improved LIF inhibition compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Several solid tumours exhibit an aberrant upregulation of JAK/STAT3 signalling via LIF autocrine or paracrine production [ 45 , 52 ] and, as shown in the present study, the LIF/LIFR pathway is represented in PDAC ( Figure 1 ). These findings are consistent with the observation that, in comparison to non-neoplastic subjects, circulating levels of LIF are significantly increased in PDAC patients and correlate with poor prognosis and cancer aggressiveness [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…Several solid tumours exhibit an aberrant upregulation of JAK/STAT3 signalling via LIF autocrine or paracrine production [ 45 , 52 ] and, as shown in the present study, the LIF/LIFR pathway is represented in PDAC ( Figure 1 ). These findings are consistent with the observation that, in comparison to non-neoplastic subjects, circulating levels of LIF are significantly increased in PDAC patients and correlate with poor prognosis and cancer aggressiveness [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…Since there are robust evidence that the LIF/LIFR pathway exerts a pro-oncogenic role in PDAC cell lines ( 13 , 20 , 55 ), and because FXR expression is increased in human PDAC tissues, we have focused our attention on the role that natural and synthetic steroids exert in modulating pancreatic cancer cell lines. For these purposes, we have first carried out a series of docking calculations on hLIFR using a small library of natural steroids ( Figure 2 ), including LCA and CDCA ( 56 ), and the semisynthetic bile alcohol steroidal agonist BAR502 ( 57 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies demonstrated that LIF blockade slow tumor progression, augment the efficacy of chemotherapy 12 , and improves therapeutic outcome 13 . Another study using a soluble version of the LIFR as a ligand trap demonstrated that blocking of LIF signaling slows tumor progression in a mouse model of pancreatic cancer 28 . Since TNBC cells express multiple LIFR ligands (LIF, OSM, and CNTF) and co-receptor gp130, aberrant induction of LIFR by HDACi has the potential to contribute to LIFR autocrine signaling loop.…”
Section: Discussionmentioning
confidence: 99%